Dosis de probiótico EM en el rendimiento y rentabilidad de aves Cobb 500 en Loreto, Perú - Sanchez Bautista, Aydeli (2024)
The research evaluated the effect of different doses of Probiotic EM on the performance and profitability of Cobb 500 birds in Loreto, Peru. A prospective, cross sectional experimental study was used, randomly assigning birds to different doses of the probiotic in a randomized whole-block design. The sample included 120 Cobb 500 birds, and production records, body weight measurements with scales, and Excel storage were used to collect data. Significant effects on performance were observed, highlighting the T2 treatment with 1 mL of probiotic per liter of water. The optimal dose was 0.9 mL per liter, achieving a feed conversion of 1.7:1 and an efficiency of 59%. T2 treatment also showed a higher economic return (47%) than other treatments. These results indicate that proper use of Probiotic EM improves poultry performance and profitability. In summary, this study offers important insights into the positive impact of MS Probiotic doses on poultry production in Loreto, with important implications for the industry and regional sustainability.